PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA KIAMA BARAT KECAMATAN MELONGUANE KABUPATEN KEPULAUAN TALAUD - Tahulending, Melvin; ROMPAS, WELSON; PALAR, NOVIE (Sam Ratulangi University, 2019)
The purpose of this research is to know the public participation in thedevelopment in the village Kiama west district Melonguane archipelago district Talaud. Thisstudy using the approach deskriptif-kualitatif. The focus of the research is participation in thedecision-making process the development of the village, and in the implementation thedevelopment of the village, in evaluation of programs of development of the village, and theutilization of the development of the village. Informants peneltian is the head of the village,chairman of the BPD, chairman of the LPM, chairman of PKK courses village, public figuresor peoples, and community members of the village kiama west, entirely amounts to 10 people.Collecting data using the guidelines interview, while the technique used is the model interactiveof Miles and Hubermann. The results of research into : (1) Public participation in the thedecision-making process the development of the village still less, which is still a lot more carriedout by the people or religion, representatives organization or groups of people, while themembers of society has not been participating. (2) Public participation in the implementation orthe implementation of the construction of a pretty high, people are generally supporting theimplementation of the development of the village which has been set to give aid or donationslike the help of cash and the material and especially donations power. (3) communityparticipation in evaluating village development programs is still lacking, i.e. it is still mostlydone by community/religious leaders, while community members are still less participating. (4)community participation in the utilization of the results of village development programs in thevillage of West Kiama is generally quite high.keywords:Â community participation, village development